Integrated nutrient management in sorghum (Sorghum bicolor) and its residual effect on wheat (Triticum aestivum) - PATIDAR, M; MALI, A L (The Indian Journal of Agricultural Sciences, 2014)
1997-98 and 1998-99 to determ ine the most appropriate combination of organic manure, fertilizers and biofertilizers for sorghum [Sorghum bioc%r (L.) Moench] and to assess their carry-over effect on succeeding wheat (Triticum aestivum L. emend. Fiori & Pao!.) crop. An application of 10 tonnes farmyard manure/ha increased grain and fodder yields of sorghum by 18.52 and 9,42%, respectively, compared with no farmyard manure application. Nuitrients uptake (N, P and K) by sorghum was also increased by 15.4, 14.2 and 16.0% respectively, with farmyard manure application. Significant improvement in grain and fodder yields was observed up to 75% recommended dose of fertilizer. Successive increase in fertility levels either 75% or 100% recommended dose of fertilizer significantly enhanced N (157.0 kg/ha), P (47 kg/ha) and K(247 kg/ha) uptake by sorghum. Inoculation. of Azospirillum alone and in combination with phosphate-solubilizing bacteria significantly increased grain and fodder yields qf sorghum. Grain and straw yields of wheat increased by 8.81 and 6.61 % owing to residul effect of farmyard manure. Application of 75% to 100% recomlnended close of ffertilizer to sorghum significantly incresed grain and straw yields of wheat. Application of farmyard manure increased net gain from sorghum;-wheat sequence by Rs 3 428/ha. Miximum net returns of Rs 49 33,51 ha were obtained from sorghum-wheat sequence under 100% recommended dose of fertilizer, followed by Rs 47 229 under 75% recommended dose of fertilizer compared with Rs 38 231 under the control. A net gaiih of RS 2 337/ha was also obtained owing to dual inoculation of Azospirillum and phosphate-solubilizing bacteria.